2017
DOI: 10.3389/fphys.2017.00070
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Mechanisms of Eccentric Contraction and Its Applications: A Role for the Giant Titin Protein

Abstract: When active muscles are stretched, our understanding of muscle function is stretched as well. Our understanding of the molecular mechanisms of concentric contraction has advanced considerably since the advent of the sliding filament theory, whereas mechanisms for increased force production during eccentric contraction are only now becoming clearer. Eccentric contractions play an important role in everyday human movements, including mobility, stability, and muscle strength. Shortly after the sliding filament th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 157 publications
1
61
0
1
Order By: Relevance
“…It has been suggested that calcium-dependent titinactin interactions may contribute to increased titin stiffness in active muscle (Herzog et al, 2016;Nishikawa, 2016;Schappacher-Tilp et al, 2015). The mechanism(s) responsible for the increase in titin stiffness during activation appear to be impaired in mdm muscles (Powers et al, 2016), and are currently under investigation (Hessel et al, 2017;Nishikawa, 2016).…”
Section: Titinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that calcium-dependent titinactin interactions may contribute to increased titin stiffness in active muscle (Herzog et al, 2016;Nishikawa, 2016;Schappacher-Tilp et al, 2015). The mechanism(s) responsible for the increase in titin stiffness during activation appear to be impaired in mdm muscles (Powers et al, 2016), and are currently under investigation (Hessel et al, 2017;Nishikawa, 2016).…”
Section: Titinmentioning
confidence: 99%
“…It is therefore likely that earlier studies (Linari et al, 2003;Pinniger et al, 2006) underestimated titin's contribution to energy storage during stretch. Increased titin stiffness in active muscle is thought to explain residual force enhancement (Leonard and Herzog, 2010;Herzog, 2014;Herzog et al, 2016;Hessel et al, 2017;Lindstedt and Nishikawa, 2017;Nocella et al, 2014). Due to its length and viscoelastic properties (Bianco et al, 2007;Mártonfalvi et al, 2014), titin is uniquely suited to store kinetic energy during stretch and also to dissipate energy as heat during shortening.…”
Section: Introductionmentioning
confidence: 99%
“…While it is beyond doubt that the chemical energy of ATP powers the cycling of myosin motors as they slide along the actin filaments during a contraction (2629), the role of titin during shortening is poorly understood and requires the sustained focus of the muscle community to be clarified. There are several competing theories for how titin might generate force during a muscle contraction (22, 3032), but experiments at the muscle fiber level have failed to elucidate a molecular mechanism. Over the last 20 years, technical advances in force spectroscopy combined with protein engineering have been used to study titin dynamics under force (10, 3339).…”
Section: Introductionmentioning
confidence: 99%
“…Mice homozygous for the mdm mutation exhibit severe and progressive degeneration of skeletal muscles and lower body mass, stiffer gait and reduced lifespan compared with wild-type (WT) littermates (Garvey et al, 2002;Huebsch et al, 2005;Lopez et al, 2008). Muscle in mdm mice has higher passive stiffness than WT muscle (Hessel et al, 2017;Lopez et al, 2008;Monroy et al, 2017). Taylor-Burt et al (2015) demonstrated in vitro that mdm mice have lower active muscle stiffness as well and a lower tremor frequency during ST.…”
Section: Introductionmentioning
confidence: 99%